2011 7th International Wireless Communications and Mobile Computing Conference 2011
DOI: 10.1109/iwcmc.2011.5982732
|View full text |Cite
|
Sign up to set email alerts
|

A design methodology for energy aware neural networks

Abstract: The increasing demand for mobile devices and high performance computing has made energy consumption a main issue in computer technology. Mobile devices require extended battery life, but the available technology still puts limits on the need for recharging the devices. High performance computing has a high price tag on energy for compute-intensive applications such as data mining. As a result, optimizations at various layers of the computer platform are becoming necessary to minimize energy usage or extend the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…We also study how the different ranges of the numbers for the kernel operation affect its energy cost. An important consequence of this finding is that it provides evidence to support assumptions made in previous work [2] when exploring alternative kernel implementations for energy saving.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…We also study how the different ranges of the numbers for the kernel operation affect its energy cost. An important consequence of this finding is that it provides evidence to support assumptions made in previous work [2] when exploring alternative kernel implementations for energy saving.…”
Section: Introductionsupporting
confidence: 78%
“…the number of times a kernel is executed, along with the corresponding kernel energy cost help in determining possible targets for energy optimizations. Further details about how to determine the kernels of the algorithms and how to know which kernel we should target for the highest energy optimizations are provided in our previous work [2].…”
Section: Kernelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a case study, we apply our suggested methodology to neural networks back-propagation (BP) (Haykin, 1998;Han and Kamber, 2006) since it is a good example of a compute-intensive application that is widely used in many domains. This paper is an extension to our previous work (Dabbagh et al, 2011), where we have tested the six-step methodology for BP, but the approach was limited to counter estimates. This paper extends the method by providing an approach for measuring actual kernel energy and then applying these measured energies instead of estimated counters.…”
Section: Introductionmentioning
confidence: 99%